A mechanistic investigation of the photoinduced, copper-mediated cross-coupling of an aryl thiol with an aryl halide. Issue 7 (14th March 2016) - Johnson, Miles W.; Hannoun, Kareem I.; Tan, Yichen; Fu, Gregory C.; Peters, Jonas C.
Abstract : A mechanistic study establishes the viability of a copper-mediated pathway for photoinduced C–S cross-coupling involving single electron transfer and in-cage radical recombination. Abstract : Photoinduced, copper-catalyzed cross-coupling can offer a complementary approach to thermal (non-photoinduced) methods for generating C–X (X = C, N, O, S, etc. ) bonds. In this report, we describe the first detailed mechanistic investigation of one of the processes that we have developed, specifically, the (stoichiometric) coupling of a copper–thiolate with an aryl iodide. In particular, we focus on the chemistry of a discrete [Cu I (SAr)2 ] − complex (Ar = 2, 6-dimethylphenyl), applying a range of techniques, including ESI-MS, cyclic voltammetry, transient luminescence spectroscopy, optical spectroscopy, DFT calculations, Stern–Volmer analysis, EPR spectroscopy, actinometry, and reactivity studies. The available data are consistent with the viability of a pathway in which photoexcited [Cu I (SAr)2 ] − * serves as an electron donor to an aryl iodide to afford an aryl radical, which then reacts in cage with the newly generated copper(ii )–thiolate to furnish the cross-coupling product in a non-chain process.